Development of Israeli mango cultivars in the Brazilian semiarid region - Maria Jany Kátia Loiola Andrade; Alexandre Santos de Oliveira; Walber Felix dos Santos; Luan dos Santos Silva; Jenilton Gomes da Cunha; Antônio Gustavo de Luna Souto; Ítalo Herbert Lucena Cavalcante (Pesquisa Agropecuária Brasileira, 2023)
Abstract The objective of this work was to evaluate the initial adaptive performance of Israeli mango tree cultivars grown in the submedian region of the São Francisco Valley, Brazil. The experiment was carried out from January 2019 to July 2020 using seedlings of the Omer and Shelly cultivars, at six months after transplanting, at a 3×6 m spacing. The experimental design was randomized complete blocks in a 2×3 factorial arrangement, corresponding to the two Israeli mango tree cultivars and the number of branches after formative pruning (three, four, and five branches), with four replicates. Biometric, biochemical, and photosynthetic variables were analyzed, differing between the evaluation times after pruning. The Omer cultivar is more vigorous than Shelly, and formative pruning with three, four, and five branches is recommended for both mango cultivars under the cultivation conditions of the São Francisco Valley.